Development and Content Validation of a Multidisciplinary Standardized Management Pathway for Hypoxemic Respiratory Failure and Acute Respiratory Distress Syndrome. (17th May 2021) - Parhar, Ken Kuljit S.; Zjadewicz, Karolina; Knight, Gwen E.; Soo, Andrea; Boyd, Jamie M.; Zuege, Danny J.; Niven, Daniel J.; Doig, Christopher J.; Stelfox, Henry T.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Treatment of hypoxemic respiratory failure and acute respiratory distress syndrome is complex. Evidence-based therapies that can improve survival and guidelines advocating their use exist; however, implementation is inconsistent. Our objective was to develop and validate an evidence-based, stakeholder-informed standardized management pathway for hypoxemic respiratory failure and acute respiratory distress syndrome to improve adherence to best practice. Design: A standardized management pathway was developed using a modified Delphi consensus process with a multidisciplinary group of ICU clinicians. The proposed pathway was externally validated with a survey involving multidisciplinary stakeholders and clinicians. Setting: In-person meeting and web-based surveys of ICU clinicians from 17 adult ICUs in the province of Alberta, Canada. Intervention: Not applicable. Measurements and Main Results: The consensus panel was comprised of 30 ICU clinicians (4 nurses, 10 respiratory therapists, 15 intensivists, 1 nurse practitioner; median years of practice 17 [interquartile range, 13–21]). Ninety-one components were serially rated and revised over two rounds of online and one in-person review. The final pathway included 46 elements. For the validation survey, 692 responses (including 59% nurses, 33% respiratory therapists, 7% intensivists and 1% nurse practitioners) were received. Agreement of greater than 75% was achieved on 43 of 46 pathway elements. Conclusions: A 46-element evidence-informed hypoxemic respiratory failure and acute respiratory distress syndrome standardized management pathway was developed and demonstrated to have content validity.